1993
DOI: 10.2737/pnw-rp-463
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the major North American needle-eating budworms.

Abstract: Data from six western States provided 1,251 life tables representing western spruce budworm, Chodstoneura occidentalis Freeman. These data provided projection capabilities for defoliation and successive budworm densities, as well as a basis for comparing survival rates among the three principal North American needle-eating budworms (western and eastern spruce budworms, and the jack pine budworm). Several modifications are suggested in current methods for managing budworm-susceptible forests, and suggestions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 103 publications
(162 reference statements)
1
36
0
Order By: Relevance
“…Several assumptions were made in calculating these rates: (1) only the current-year foliage was damaged (many herbivores prefer the youngest needle tissue of conifers (Miller et al 1991, Campbell 1993, Mc-Cullough et al 1993, Carisey and Bauce 1997, Clancy et al 1998a; (2) the herbivores damaged the needles according to the pattern we observed in the laboratory where only a distal portion of the needle is initially removed by the herbivore, leaving the remaining portion of the needle damaged on the tree for a period of time (Litvak and Monson 1998); (3) the change in monoterpene fluxes from wounded needles over an 8d period follows the pattern described in Litvak and Monson (1998); and (4) the simulations will only tell us the potential impact herbivory could have on local tropospheric chemistry during an outbreak.…”
Section: The Analytical Box Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Several assumptions were made in calculating these rates: (1) only the current-year foliage was damaged (many herbivores prefer the youngest needle tissue of conifers (Miller et al 1991, Campbell 1993, Mc-Cullough et al 1993, Carisey and Bauce 1997, Clancy et al 1998a; (2) the herbivores damaged the needles according to the pattern we observed in the laboratory where only a distal portion of the needle is initially removed by the herbivore, leaving the remaining portion of the needle damaged on the tree for a period of time (Litvak and Monson 1998); (3) the change in monoterpene fluxes from wounded needles over an 8d period follows the pattern described in Litvak and Monson (1998); and (4) the simulations will only tell us the potential impact herbivory could have on local tropospheric chemistry during an outbreak.…”
Section: The Analytical Box Modelmentioning
confidence: 99%
“…In temperate forests during non-outbreak periods, defoliators regularly consume 5-15% of the leaf area produced (Schowalter et al 1986, Landsberg andOhmart 1989). Yet foliage losses can reach 25-100% in herbivore outbreak years (Kulman 1971, Furniss and Carolin 1977, Schowalter et al 1986, Mattson et al 1991, Campbell 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Second, warm and dry conditions characteristic of drought create a physical environment that increases larval survival (Rhoades , Mattson and Haack ), where larval survival, growth, and reproductive rates are greater during periods of low precipitation, foliar moisture content, and/or soil moisture (Cates et al. , Mattson and Haack , Clancy , Campbell ).…”
Section: Discussionmentioning
confidence: 99%
“…The program applies a set of userdefined criteria to identify sustained periods of reduced radial growth associate with insect outbreak intervals (Holmes and Swetnam 1996). Following the approach previously taken in this region (Axelson et al 2015) and in comparable environments (Swetnam and Lynch 1989, 1993, Ryerson et al 2003, Alfaro et al 2014, WSB outbreaks were identified where (1) a minimum threshold of eight years of below-average growth was detected and (2) there was a trend of reduced growth below À1.28 standard deviation. Standwide outbreaks were defined as occurring when at least 40% of host trees recorded defoliation (Flower et al 2014a).…”
Section: Disturbance History Reconstructionsmentioning
confidence: 99%
See 1 more Smart Citation